A multinuclear magnetic resonance study of the kinetics and mechanisms of dissociation of cation complexes with ionophores. - Smith, Helen Patricia Graves. (University of Ottawa (Canada), 1991)
The behaviour of the cation - ionophore complexes in solution has been studied by $\sp{23}$Na, $\sp{43}$Ca and $\sp $C NMR. $\sp{23}$Na NMR is an ideal tool for investigating the decomplexation of such complexes. The (Na-DB24C8)$\sp+$ and (Na-18C6)$\sp+$ complexes form quantitatively (K$\sb{\rm f} > 10\sp5$) and may decomplex by either the dissociative or the metal associative interchange "M$\sb{\rm ai}$" mechanisms. The (Na-DB24C8)$\sp+$ system follows the M$\sb{\rm ai}$ mechanism when either BPh$\sb4\sp-$ or PF$\sb6\sp-$ is the counter anion. The concentration of the counter anion does not influence the mechanism, but at higher concentrations the rate is slightly accelerated. The (Na-18C6)$\sp+$ has been examined in AC (acetone), AN (acetonitrile), NM (nitromethane), PC (propylene carbonate), and PY (pyridine), with BPh$\sb4\sp-$ as the counter anion. The dissociative mechanism is the only one operative in AC. The two mechanisms compete in AN, PC and PY. The kinetic parameters for the dissociative process have been calculated in these four solvents, while in PC the kinetic parameters of the M$\sb{\rm ai}$ mechanism were also accessible. An entropy-enthalpy effect was observed. In NM a kinetic study is precluded by the small difference in chemical shifts between free and complexed species. The influence of the counter anion was studied by examining the changes which result when SCN$\sp-$ replaces BPh$\sb4\sp-$ for the (Na-18C6)$\sp+$ system in AC. With BPh$\sb4\sp-$, only the dissociative mechanism is operative, so if the presence of SCN$\sp-$ were to change the mechanism this would be easily identifiable. Ion-pairing must be considered. All of the species were characterized, and the ion-pairing rate constants for the cation and complex were determined. The contributions to the observed rate constant could then be separated. The ion-paired complex, though 2.3 $\pm$ 0.4 kJ.mol$\sp{-1}$ less stable, has a lower activation barrier (47.2 $\pm$ 0.2 kJ.mol$\sp{-1}$ as compared to 49.5 $\pm$ 0.2 kJ.mol$\sp{-1})$ and the faster rate of dissociation. $((4.2 \pm 0.3) \times 10\sp4\rm{s}\sp{-1}$ as compared to $(1.6 \pm 0.2) \times 10\sp4\rm{s}\sp{-1})$ The presence of SCN$\sp-$ accelerates the rate of the dissociative mechanism, rather than introducing another. The $\sp{23}$Na quadrupolar coupling constant is not accessible by $\sp{23}$Na NMR. With the aid of $\sp $C NMR, and based on the assumption that the $\tau\sb{\rm eff}$ measured for 18C6 is equivalent to the $\tau\sb{\rm c}$ of the $\sp{23}\rm{Na}\sp+$ it is complexing, a measure of the symmetry about the $\sp{23}\rm{NA}\sp+$ is obtained. In AC, AN, and PC this environment is quite symmetrical ($\chi\sim$ 1.0-1.2 MHz). In PY the highly donating solvent competes with crown ether oxygens and in NM the high internal pressure of the solvent both lead to distortions of the complex from high symmetry and higher $\chi$ values result. Lasalocid, a naturally-occurring ionophore, complexes with Na$\sp+$ cations. This compound can serve as both ligand and counter anion so the approach used for the (Na-18C6)$\sp+$ system gives some information, but does not describe it completely. The dissociative mechanism is operative in PY but other interactions are present. The tetra-carboxylic acid substituted 18crown6 (18C6A$\sb4$) was also studied in PY. Interactions between the Na$\sp+$ and 18C6A$\sb4$ were observed by $\sp{23}$Na NMR but were not quantified. The $\sp{43}$Ca nucleus is not as well-suited for NMR studies as $\sp{23}$Na, since it is of low abundance and resonates at low frequencies. Despite these potential drawbacks an exploratory study in 50:50 AC:H$\sb2$O was made. The titration of $\sp{43}$Ca$\sp{++}$ by 18C6 could be followed, and the formation constant (K$\sb{\rm f}$) was found to be 10 $\pm$ 3.
Keywords: Chemistry, Physical.